Mesenchymal Stromal Cell-Derived Extracellular Vesicles Reduce Neuroinflammation, Promote Neural Cell Proliferation and Improve Oligodendrocyte Maturation in Neonatal Hypoxic-Ischemic Brain Injury - Kaminski, Nicole; Köster, Christian; Mouloud, Yanis; Börger, Verena; Felderhoff-Müser, Ursula; Bendix, Ivo; Giebel, Bernd; Herz, Josephine (Frontiers in Cellular Neuroscience, 2020)
Background: Neonatal encephalopathy caused by hypoxia-ischemia (HI) is a major cause of childhood mortality and disability. Stem cell-based regenerative therapies seem promising to prevent long-term neurological deficits. Our previous work in neonatal HI revealed an unexpected interaction between mesenchymal stem/stromal cells (MSCs) and the brains’ microenvironment leading to an altered therapeutic efficiency. MSCs are supposed to mediate most of their therapeutic effects in a paracrine mode via extracellular vesicles (EVs), which might be an alternative to cell therapy. In the present study, we investigated the impact of MSC-EVs on neonatal HI-induced brain injury. Methods: Nine-day-old C57BL/6 mice were exposed to HI through ligation of the right common carotid artery followed by one hour hypoxia (10% oxygen). MSC-EVs were injected intraperitoneally 1, 3 and 5 days after HI. One week after HI, brain injury was evaluated by regional neuropathological scoring, atrophy measurements and immunohistochemistry to assess effects on neuronal, oligodendrocyte and vessel densities, proliferation, oligodendrocyte maturation, myelination, astro- and microglia activation. Immunohistochemistry analyses were complemented by mRNA expression analyses for a broad set of M1/M2- and A1/A2-associated molecules and neural growth factors. Results: While total neuropathological scores and tissue atrophy were not changed, MSC-EVs significantly protected from HI-induced striatal tissue loss and decreased micro- and astroglia activation. MSC-EVs lead to a significant downregulation of the pro-inflammatory cytokine TNFa, accompanied by a significant upregulation of the M2 marker YM-1 and the anti-inflammatory cytokine TGFb. MSC-EVs significantly decreased astrocytic expression of the A1 marker C3, concomitant with an increased expression of neural growth factors (i.e. BDNF, VEGF and EGF). These alterations were associated with an increased neuronal and vessel density, coinciding with a significant increase of proliferating cells in the neurogenic sub-ventricular zone juxtaposed to the striatum. MSC-EV-mediated neuroprotection went along with a significant improvement of oligodendrocyte maturation and myelination. Conclusion: The present study demonstrates that MSC-EVs mediate anti-inflammatory effects, promote regenerative responses and improve key developmental processes in the injured neonatal brain. The present results suggest different cellular target mechanisms of MSC-EVs, preventing secondary HI-induced brain injury. MSC-EV treatment may be a promising alternative to risk-associated cell therapies in neonatal brain injury.